Effects of Onpi-To (One of Herb Medicine) on Production of Active Oxygen Species from Neutrophils in Hemodialysis Patients - Ninomiya, Hiroyuki; Saheki, Shuichi; Shinohara, Rikio; Ishiguro, Isao; Tokunaga, Kenji; Takeuchi, Nozomu; Mistuma, Tadamichi; Murase, Mitsuharu; Kanno, Kazuhisa (Japanese Journal of Clinical Chemistry, 1995)
Hemodialysis patients (HD) were treated with onpi-to (an herb medicine) administration, and the changes in active oxygen production by neutrophils, and serum superoxide dismutase activities and methylguanidine levels were examined throughout the treatment. The active oxygen production by neutrophils was measured by a flow-cytometric technique or by a cytochrome c reduction method. The active oxygen production was greater in the neutrophils of the HD patients than in normal subjects with or without phorbol myristate acetate (PMA) stimulation. Superoxide dismutase activities and methylguanidine levels in the serum of HD patients were reduced by the treatment. An in vitro experiment using neutrophils from normal subjects showed that onpi-to suppressed stimulated active oxygen production by phorbol myristate acetate, but not by N formyl-methionyl-leucyl-phenylalanine (fMLP) or opsonized zymosan (OZ).